Decree of the Prime Minister No. 3050 of the Year 2016 With Regard to Granting the Existing Factories Temporary Industrial Licenses for One Year Pending the Adjustment of their State of Affairs = قرار رئيس مجلس الوزراء رقم 3050 لسنة 2016 فى شأن منح المصانع القائمة تراخيص صناعية مؤقتة لمدة عام وذلك إلى حسين توفيق أوضاعها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic